Confinement effect on thermopower of electrolytes. (March 2022) - Qian, Xin; Liu, Te-Huan; Yang, Ronggui
Abstract: Ionic Seebeck effect of electrolytes has shown promising applications in harvesting energy from low-grade heat sources with small temperature differences from the environment, which can power sensors and Internet-of-Things devices. Recent experiments have demonstrated giant thermopower (∼10 mV/K) of electrolytes under confinement due to the overlapping of electric double layer (EDL). Nonetheless, there has been no consensus on the theory of the ionic Seebeck effect, especially whether the thermopower depends on ionic diffusivities, imposing confusion on the theoretical interpretation of experimental discoveries of the giant thermopower of confined electrolytes. This article presents a linear perturbative solution of Poisson-Nernst-Planck (PNP) equations to describe the ionic Seebeck effect of confined liquid electrolytes. We provide analytical and numerical solutions to the PNP equations for both closed systems and open systems connected to reservoirs of electrolytes. The analytical solution captured the confinement effect both along and perpendicular to the temperature gradient, and showed excellent agreement with numerically solved PNP equations for a wide range of EDL potentials, channel widths, and lengths. Finally, we show that for polyelectrolytes with largely mismatched diffusivities, thermopower can only be enhanced for the closed system through confinement perpendicular to the temperature gradient. Graphical abstract: Image 1 Highlights: Ionic thermopower for confined electrolytes have been analytically derived. Diffusivity dependence of ionic thermopower has been comprehensively discussed. Thermopower of polyelectrolyte can only be enhanced for closed system through confinement.